Образ Григорія Сковороди в поетичних інтерпретаціях Павла Тичини і Василя Стуса - Гаврилюк, Н. (Слово і Час, 2022)
У статті проаналізовано образ Григорія Сковороди в поезії П. Тичини й
В. Стуса. Зіставлення творів дає змогу не тільки побачити спільне і відмінне в зображенні цієї постаті (порівняльний аспект), а й зауважити
причини тієї чи тієї інтерпретації (історичний аспект). У П. Тичини
Г. Сковорода постає революціонером, що стоїть на засадах класової ідеології. У В. Стуса — філософом, що вболіває за долю всього українського народу. The comparison of works by P. Tychyna and V. Stus allows us not only to see the common
and different in the interpretation of Hryhorii Skovoroda (comparative aspect) but also to
notice the reasons for one or another interpretation (historical aspect).
In P. Tychyna’s works H. Skovoroda is inscribed in the character’s historical time (Koliivshchyna)
in the same way as the author of the poem is inscribed in his historical reality
(Sovietism), while in V. Stus’s poems both the character and the author are outside their time
(Koliivshchyna and Sovietism respectively). For both poets — H. Skovoroda and V. Stus —
the external appeared as transient, and ‘the inner man’ had the status of eternal one.
P. Tychyna and V. Stus use the image of Н. Skovoroda as their alter-ego. The former
author describes Н. Skovoroda as a revolutionary who stands on the principles of class ideology.
Tychyna had been writing his poem-symphony “Skovoroda” in the period from the
formation of Soviet power to the time of Stalinism as its most brutal version. This poemsymphony
is a tribute to the time, which helped him phisically survive.
In V. Stus’s version, Н. Skovoroda is thinking about moral self-improvement. He is a
philosopher who cares for the fate and future of the Ukrainian people. V. Stus, living under
the Soviet system, did not accept it and put up a strong resistance to it as a representative
of the sixtiers. Stus’s poetry considered in this article may be regarded as a polemic with
the poem-symphony “Skovoroda” by P. Tychyna. Moreover, the poem “Introduction to the
poem “Skovoroda” by V. Stus shows that this polemic was planned in the format of the same
genre — the poem, although it never unfolded, remaining only in fragments.
Tychyna’s work also has a fragmentary nature due to both the long time of writing and
the two-layered image of H. Skovoroda. The poet tried to show Skovoroda as a philosopher
and a revolutionary (with the dominance of the latter).